Clinical analysis of eosinophilic gastroenteritis in 71 children - Han, X X (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2018)
Objective: To summarize the clinical data including manifestations, diagnosis, treatment and prognosis of eosinophilic gastroenteritis (EGE) in children. Methods: A retrospective analysis was performed in 71 patients with pathologically proven EGE at Beijing Children's Hospital Affiliated to Capital Medical University from January 2008 to January 2017. Their clinical manifestations, laboratory and imaging examinations, endoscopic findings, histopathological examinations, and treatment were collected and analyzed. Results: Among 71 EGE cases, 47 (66%) cases were male and 24 (34%) cases were female, and the median age was 9.2 (0.2-16.5) years old. The main clinical manifestations included abdominal pain (76%, 54/71), vomiting (68%, 48/71), anorexia (54%, 38/71), weight loss (38%, 27/71), and diarrhea (37%, 26/71). There were 27 cases (38%) with a history of allergic diseases or family history. The median absolute value of eosinophil in peripheral blood of the 71 patients was 0.4 (0-36.8)×10(9)/L, and 27 cases (38%) showed an increase in eosinophil counts. Serum IgE was measured in 52 patients (104.3 (3.4- 3 000.0)×10(3) U/L), and 30 patients (58%) showed an increase in serum IgE. A large number of eosinophils ((41.0±8.5)/HP) were found in 3 patients' ascites. The endoscopic examination of upper gastrointestinal tract revealed hyperemic edema in 62 cases (87%), plaque in 44 cases (62%), erosion in 17 cases (24%) and ulceration in 16 cases (23%). Histopathologically, in 8 cases (11%) the disease involved both stomach and duodeneum, in 21 cases (30%) involved stomach only, and in 37 cases (52%) involved duodeneum only. In addition, in 6 cases (8%) the disease involved esophagus and in 10 cases (14%) involved colorectum. Microscopically, eosinophil counts averaged 67/HP, 33/HP, 40/HP and 38/HP in esophageal, gastric, duodenal and colorectal mucosa respectively. A total of 34 cases were treated with glucocorticoid, and all these patients had alleviation of symptoms, which occurred within 14.9 days on average, but EGE recurred in 11 cases (32%). Conclusions: The clinical symptoms and endoscopic findings of EGE are diverse and nonspecific. Histopathological examination of gastrointestinal mucosa is particularly important for the diagnosis. Glucocorticoid treatment is effective, but the patients with EGE are prone to relapse